2011
DOI: 10.1017/s1368980010003253
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural correlates of active commuting to school in Spanish adolescents: the AFINOS (Physical Activity as a Preventive Measure Against Overweight, Obesity, Infections, Allergies, and Cardiovascular Disease Risk Factors in Adolescents) study

Abstract: Objective: To examine the associations between lifestyle factors and active commuting to school in Spanish adolescents. Design: Cross-sectional study. Lifestyle factors (overall/extracurricular physical activity, television viewing, reading as a hobby, sleep duration, breakfast/fruit intake, smoking and alcohol intake) as well as mode and duration of commuting to school were self-reported. Active commuters were defined as those adolescents who walked or cycled to school. Setting: Secondary schools in Madrid, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
5
24
0
8
Order By: Relevance
“…Higher rates of active commuting, between 76% and 90%, were found in Switzerland and Norway , and similar percentages to those obtained in the current study were found in Belgium and China . Despite the lack of studies reporting percentages of active commuting to school in Spain, Spanish adolescents aged 13‐17 showed similar percentages of active commuting than those obtained in this study for children aged 10‐12 years . Moreover, children aged 8‐9 years and 10‐12 years had increased safety perceptions of 41% and 62%, respectively, compared to 10% in children aged 6‐7 years.…”
Section: Discussionsupporting
confidence: 85%
“…Higher rates of active commuting, between 76% and 90%, were found in Switzerland and Norway , and similar percentages to those obtained in the current study were found in Belgium and China . Despite the lack of studies reporting percentages of active commuting to school in Spain, Spanish adolescents aged 13‐17 showed similar percentages of active commuting than those obtained in this study for children aged 10‐12 years . Moreover, children aged 8‐9 years and 10‐12 years had increased safety perceptions of 41% and 62%, respectively, compared to 10% in children aged 6‐7 years.…”
Section: Discussionsupporting
confidence: 85%
“…There is no previous evidence that directly associates household electronic media presence and active commuting. However electronic media use is negatively associated with sleep quality [ 34 36 ], and adequate sleep duration is associated with greater active commuting to school [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides being overweight, the presence of other CVD risk factors have been reported and associated with the level of physical activity in adolescents (Martínez-Gómez et al 2011). Thus, proposals of classifications for the number of steps/day considering different CVD risk factors should be performed providing information on its ability for screening each of these factors.…”
Section: Number Of Steps/day and Cardiovascular Healthmentioning
confidence: 99%